Lifetime imaging of the discrete nanophosphors in biological systems - A. O. Zvyagintcev; A. V. Yudintsev; A. Maleki; V. A. Vodeneev; A. V. Zvyagin (Сеченовский вестник)
The aim. Demonstrate a novel modality of laser-scanning multiphoton microscopy suitable for rapid acquisition of images of samples labelled with phosphorescent materials characterised by long emission lifetime measured in microseconds. The reported microscopy represents an advancement over the existing laser-scanning modalities, where the acquisition of images of phosphorescent materials takes unpractically long time.Materials and methods. The reported method is based on rapid scanning of the focussed excitation beam across a sample while continuously recording the photoluminescent (PL) signal. The resultant images of discrete phosphorescent nanoparticles appeared blurred. The diffraction-limited image was reconstructed by using a deconvolution algorithm, where the PL lifetime was the key input parameter. To test the method, two types of upconversion nanoparticles (UCNP) were synthesised, NaYF4:Yb3+:Er3+/NaYF4 (E-UCNP), β-NaYF4:Yb3+, Tm3+/NaYF4 (T-UCNP) and used to test a possibility of demultiplexing the two types of UCNPs ex vivo taken up in the mouse liver.Results. The resultant images of E-UCNP, T-UCNP on the background of the liver were fully reconstructed and exhibited the enhanced signal-to-noise ratio. Besides, the method allowed rapid (at the scale of seconds) acquisition of the UCNP PL lifetime and clear discrimination of the two types of UCNPs.Conclusion. We demonstrated a new approach for rapid PL image acquisition of samples containing PL materials, such as biological specimens labelled with discrete UCNPs. Blurred images were shown to be reconstructed at the post-processing stage by applying a deconvolution procedure. This enabled demonstration of multiplexing/demultiplexing using lifetime imaging mode, where the lifetime was engineered by the UCNP synthesis and reconstructed during multiphoton image acquisition using the deconvolution algorithm. The power of this method was demonstrated by the identification of two types of UCNPs accumulated in the liver of a laboratory animal. We believe that the demonstrated method can be useful for rapid lifetime imaging where several molecular specific labelling agents are required.